2019
DOI: 10.1017/s0144686x19001387
|View full text |Cite
|
Sign up to set email alerts
|

‘A lonely old man’: empirical investigations of older men and loneliness, and the ramifications for policy and practice

Abstract: Loneliness has become an issue of significant academic, public and policy focus. There has been much research on experiences of loneliness in later life and many accompanying interventions targeting lonely older people. However, there has been a dearth of research on the impact that loneliness can have on older men and the resulting implications for policy and practice. This paper aims to redress this by developing a theoretical framework to improve understanding of older men's constructions and experiences of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…Markers and experiences in our lives, such as retirement, bereavement, illness, disability or caring responsibilities, can be triggers to loneliness. With this in mind, the COVID-19 pandemic has exacerbated loneliness and social isolation amongst society, not only amongst older populations (Drennan et al, 2008;Ejlskov et al, 2020;Marston & Morgan, 2020;Yang & Victor, 2011), but also younger cohorts (Ejlskov et al, 2020), young disabled adults (Morris, 2001), men (Ratcliffe et al (2019) and childless adults who in/voluntary experience childlessness (Hadley, 2020;Hadley, 2018a;Hadley, 2018b;Hadley, 2019). Hadley (2018b) argues, "While many age related issues such as isolation, loneliness and dementia have recently gathered extensive attention (and funding) people ageing without children is a subject that remains unreported, under-researched and under-represented at all levels" (Hadley, 2018b, p. 76-77).…”
Section: Intergenerational Social Connectedness and Lonelinessmentioning
confidence: 99%
“…Markers and experiences in our lives, such as retirement, bereavement, illness, disability or caring responsibilities, can be triggers to loneliness. With this in mind, the COVID-19 pandemic has exacerbated loneliness and social isolation amongst society, not only amongst older populations (Drennan et al, 2008;Ejlskov et al, 2020;Marston & Morgan, 2020;Yang & Victor, 2011), but also younger cohorts (Ejlskov et al, 2020), young disabled adults (Morris, 2001), men (Ratcliffe et al (2019) and childless adults who in/voluntary experience childlessness (Hadley, 2020;Hadley, 2018a;Hadley, 2018b;Hadley, 2019). Hadley (2018b) argues, "While many age related issues such as isolation, loneliness and dementia have recently gathered extensive attention (and funding) people ageing without children is a subject that remains unreported, under-researched and under-represented at all levels" (Hadley, 2018b, p. 76-77).…”
Section: Intergenerational Social Connectedness and Lonelinessmentioning
confidence: 99%
“…The notion of being/feeling insufficiently masculine as a cause of loneliness, though, would appear to suggest a complex situation where being emotionally candid can be a cause of loneliness too. Nevertheless, some studies, albeit all of which were focused on older men, have suggested this can be overcome, particularly in social settings where men can take part in 'constructive' activities inflected with a 'supportive' atmosphere (46,75,76,78,89).…”
Section: Discussionmentioning
confidence: 99%
“…A £10 gift voucher was offered for taking part. To maintain anonymity, demographic data is not linked to participant pseudonyms (Bell 2010;Ratcliffe et al 2019).…”
Section: Samplementioning
confidence: 99%
“…However, they remained a less positive substitute for 'face-to-face' interaction, therefore long term use without face-to-face interactions may constitute a component of 'lockdown fatigue' (Mahase 2020;Goldstein et al 2021). Ratcliffe et al (2019) posit that older men may place a sense of 'social worth' as critical to preventing loneliness, and emphasise that this does not always require social contact. The notion of 'loneliness with a purpose' may represent a stark example of this, although Kamin et al's (2021) study of sololiving women in Slovenia also found they related a moral responsibility to reduce transmission, albeit without suggesting this reduced loneliness.…”
Section: Anxiety Of Social Contactmentioning
confidence: 99%